Hydrogen Sulfide Suppress the Pathological Alterations of Endocrine Glands Induced by Gamma Irradiation and Cyclophosphamide - Kassem, Ashraf (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2022)
Background: Hydrogen sulfide (H2S) is a gaseous mediator and is usually recommended to have antioxidant, anti-inflammatory, anticancer, and antiapoptotic consequences. In the endocrine system, H2S can act at the thyroid, adrenal gland, and gonad through the hypothalamus–pituitary axis, in addition to at the pancreas, thereby collaborating within side the law of many hormones of the body, and the hypothalamus–pituitary axis can, in turn, adjust the manufacturing of H2S. Chemotherapy Cyclophosphamide can cause damage of thyroid, pituitary, pancreatic, and adrenal glands. Radiation-induced thyroid, hypothalamus, and anterior pituitary gland disorders. Radiation-induced injury of the endocrine pancreas is known to increase the risk of diabetes mellitus (DM). Testis tissue, radiosensitive organ, has a variety of cells that differ in their degree of sensitivity. In this manner, cancer patient needs for protective agent against different side effects of anticancer therapy, especially in case of combination between chemo and radio therapies. Presentation of the Hypothesis: H2S can guard endocrine organs and adjust hormone secretion through antioxidative effect and ion channel regulation. H2S performs a function withinside the endocrine system to guard pancreatic cells, adjust insulin secretion, hold the characteristic of the adrenal cortex, sell the discharge of catecholamine, and adjust the secretion of pituitary hormones. Implications of the Hypothesis: Administrations of H2S has protecting and therapeutic results on endocrine glands in opposition to numerous results of chemo- and radiotherapies. H2S is a promising molecule for the development of new medications.